2001
DOI: 10.1097/00000539-200105000-00034
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of 0.0625% Bupivacaine with Fentanyl and 0.1% Ropivacaine with Fentanyl for Continuous Epidural Labor Analgesia

Abstract: We compared different concentrations of epidural bupivacaine and ropivacaine thought to be equipotent. Both solutions were equally efficient in providing highly effective epidural analgesia for labor with minimal motor block. These findings suggest that bupivacaine may be more potent than ropivacaine.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
19
2

Year Published

2003
2003
2018
2018

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(31 citation statements)
references
References 14 publications
10
19
2
Order By: Relevance
“…This correlated with the previous study by Jaime Fernandez et al, 6 wherein there was no prolongation of first stage of labour between Group B -401 ± 184 min and Group R -365 ± 186 min with no statistical significance.…”
Section: Duration Of First Stage Of Laboursupporting
confidence: 92%
See 3 more Smart Citations
“…This correlated with the previous study by Jaime Fernandez et al, 6 wherein there was no prolongation of first stage of labour between Group B -401 ± 184 min and Group R -365 ± 186 min with no statistical significance.…”
Section: Duration Of First Stage Of Laboursupporting
confidence: 92%
“…The haemodynamic parameters correlated with the previous study by Pirbudak et al, 10 and Jaime Fernandez et al, 6 were there was no statistical significance in haemodynamic parameters.…”
Section: Haemodynamic Parameterssupporting
confidence: 85%
See 2 more Smart Citations
“…In our study, no patients developed bradycardia or respiratory depression in either group. Campbell et al [13] observed that there was no incidence of hypotension in either group (bupivacaine (0.08%)/fentanyl vs. ropivacaine (0.08%)/ fentanyl) whereas Fernández-Guisasola et al [6] compared the 0.0625% bupivacaine with 0.1% ropivacaine with fentanyl as an epidural infusion and observed 2 patients in bupivacaine group and 1 patient in ropivacaine group required ephedrine for hypotension. In this study, there was no incidence of pruritus in either group.…”
Section: International Journal Of Medical Science and Public Healthmentioning
confidence: 99%